Efektivitas Penggunaan Metode Fonik Terhadap Peningkatan Kemampuan Membaca Permulaan Siswa Tunagrahita Kelas III di SLB Negeri 1 Tapin - Jarniah Jarniah (Universitas 45 Surabaya, 2023)
In the learning process, mentally retarded students still have difficulties because they are influenced by memory and perception factors. Reading is a complex activity because it involves physical and mental activities. This research aims to determine the improvement in reading ability of mentally retarded students using the phonics method. The method in this research is Classroom Action Research (PTK). The subjects of this research were 5 students. The research was carried out in 2 cycles and data collection techniques included tests, observation and documentation. The results of the study showed an increase in beginning reading abilities in students with intellectual disabilities.